First Do No Harm - Then, Build Trust : Anti-Corruption Strategies in Fragile Situations - Johnston, Michael (Washington, DC: World Bank, 2012)
Most familiar anti-corruption strategies require sound state, social, and political institutions, and a minimal level of trust, both in government and among citizens. The absence of all or most of those assets is in part what defines fragility. Another key attribute is an 'expectations trap', in which citizens expect very little of government and government demands very little of citizens, as long as they stay out of the way; in those situations fragility can become a persistent situation. Using the Stresses-Capabilities-Expectations framework, this paper analyzes the possibilities and risks of reform in fragile situations. Reformers should be aware of contrasts among kinds of corruption problems, and of the potential benefits of 'halfway' reform outcomes. The first priority ('Do no harm') means avoiding premature or poorly-thought-out reforms that can do more harm than good--notably, steps that overwhelm a society's capacity to absorb aid and put it to effective use, and that risk pushing fragile situations and societies into particular kinds of corruption that are severely disruptive. The second imperative ('Build trust') is essential if complex collective-action problems are to be minimized, and if reform is to draw broad-based support. A first step toward greater trust is to provide basic services--particularly those in which broad segments of society share a stake--in credible and demonstrable ways. Then, gradual but balanced enhancements to participation (a variety of stress) and institutions can build opposition to corruption, in a climate of growing trust. Reform in the end involves rebalancing stresses and capabilities so that expectations can change in positive ways. The best ways to demonstrate and assess anti-corruption progress is to examine kinds of behavior, in civil society as well as in politics and the economy, that reflect improving climates of expectations and trust.